Nanoethosomes for Dermal Delivery of Lidocaine - Soraya Babaie; Saeed Ghanbarzadeh; Soodabeh Davaran; Maryam Kouhsoltani; Hamed Hamishehkar (Tabriz University of Medical Sciences, 2015)
Purpose: It is necessary for local anesthetics to pass through the stratum corneum to provide rapid pain relief. Many techniques have been reported to enhance intradermal penetration of local anesthetics such as vesicular lipid carriers. Ethosomes are lipid vesicles containing phospholipids, ethanol at relatively high concentration. We hypothesized that synergistic effects of phospholipids and high concentration of ethanol in formulation could accelerate penetration of nanoethosomes in deep layers of skin. Methods: Lidocaine-loaded nanoethosomes were prepared and characterized by size and zeta analyzer, scanning electron microscopy (SEM) and X-ray diffractometer (XRD). Furthermore, encapsulation efficiency (EE), loading capacity (LC), and skin penetration capability were evaluated by in vitro and in vivo experiments. Results: results showed that the particle size, zeta potential, EE and LC of optimum formulation were 105.4 ± 7.9 nm, -33.6 ± 2.4 mV, 40.14 ± 2.5 %, and 8.02 ± 0.71 respectively. SEM results confirmed the non-aggregated nano-scale size of prepared nanoethosomes. Particle size of ethosomes and EE of Lidocaine were depended on the phospholipid and ethanol concentrations. XRD results demonstrated the drug encapsulation in amorphous status interpreting the achieved high drug EE and LC values. In vitro and in vivo assays confirmed the appropriate skin penetration of Lidocaine with the aid of nanoethosomes and existence of deposition of nanoethosomes in deep skin layers, respectively. Conclusion: The developed nanoethosomes are proposed as a suitable carrier for topical delivery of anesthetics such as Lidocaine.